#### Corey Franklin

##### New member

- Joined
- Sep 20, 2006

- Messages
- 3

2v+18=16-4v-28

18=16+6v-28

2=6v-10

0=6v-12

0=v-6

???

4x-(9-3x)=8x-1

4x-12x=8x-1

8x=8x-1

x=-1

- Thread starter Corey Franklin
- Start date

- Joined
- Sep 20, 2006

- Messages
- 3

2v+18=16-4v-28

18=16+6v-28

2=6v-10

0=6v-12

0=v-6

???

4x-(9-3x)=8x-1

4x-12x=8x-1

8x=8x-1

x=-1

- Joined
- Apr 12, 2005

- Messages
- 9,790

Whoops. Subtracting 2v makesCorey Franklin said:2v+18=16-4v-28

18=16+6v-28

Whoops. Left side should be 4x - 9 + 3x. Where did you get 12x? 9+3? Don't do that.4x-(9-3x)=8x-1

4x-12x=8x-1

Give them another go.

- Joined
- Sep 20, 2006

- Messages
- 3

2v+18=16-4(v+7)

2v+18=16-4v-28

18=16-2v-28

2=2v-12

2v-10

v=-5

I know I shouldn't have added the 9 and the 3, guess I was too tired...

4x-(9-3x)=8x-1

4x-9+3x=8x-1

7x-9=8x-1

-9=1x-1

-8=1x

x=-8

Corey Franklin said:Well, I think I did better on one of them; still confused on the other...

2v+18=16-4(v+7)

2v+18=16-4v-28 you are correct up to this point.

Now, simplify the right-hand side by combining like terms:

2v + 18 = -4v - 12

Eliminate the variable term from one side.....it LOOKS like you have attempted to eliminate the 2v from the left side, which is ok. BUT, you'd need to add -2v to both sides to do that:

2v + 18 + (-2v) = -4v - 12 + (-2v)

18 = -6v - 12

Now, get the variable term by itself. To eliminate the " - 12" from the right side, ADD 12 to both sides:

18 + 12 = -6v - 12 + 12

30 = -6v

Divide both sides by -6:

30 / (-6) = (-6v) / (-6)

-5 = v

CHECK YOUR ANSWER. Is the original equation true when we substitute -5 for v?

2(-5) + 18 = 16 - 4(-5 + 7)

-10 + 18 = 16 - 4(2)

8 = 8 True. It checks.

18=16-2v-28 This step is incorrect and so is everything that follows this step.

2=2v-12

2v-10

v=-5 this is the correct answer, but IT DOES NOT COME from the work you've shown! (maybe it came from the back of the book??).

I know I shouldn't have added the 9 and the 3, guess I was too tired...

4x-(9-3x)=8x-1

4x-9+3x=8x-1

7x-9=8x-1

-9=1x-1

-8=1x

x=-8